ANALISIS PELAKSANAAN PRINSIP GOOD CORPORATE GOVERNANCE DALAM PERSPEKTIF ISLAM (STUDI KASUS PADA BANK SUMUT SYARIAH KCP KARYA) - Pulungan, Rahmat Rizki; Sabila, Sarah; Ardiah, Inayah; Daulay, M. Iqbal (Jihbiz: Global Journal of Islamic Banking and Finance, 2024)
This research is aimed at analyzing the implementation of good corporate governance principles from the perspective of Islamic law. This type of research is field research with a descriptive qualitative approach. This research was conducted at Bank Sumut Syariah KCP Karya. The methods used are interviews and documentation. The results of this research indicate that the implementation of the principles of good corporate governance at Bank Sumut Syariah KCP Karya is in accordance with the perspective of Islamic law. The principle of transparency is in accordance with QS. al-Baqarah verses 188 and 282, the principle of accountability in accordance with QS. al-Baqarah verse 197 and QS. an-Nisa verse 58, the principle of compliance in accordance with QS. al-Mudatsir verse 38, the principle of independence is in accordance with the hadith narrated by Abu Ya'la and authenticated by Albani and the principle of equality is in accordance with the QS. an-Nahl verse 90.